Molecular characterization of NADPH oxidase genes and expression of marbohB1 gene in response to fungal pathogen Fusarium oxysporum f. sp. cubense in banana - Chai, Siew Ying (2019)
Plant NADPH oxidases or also known as respiratory burst oxidase homolog (rboh) catalyzes the production of reactive oxygen species (ROS) which play crucial roles in plant development, hormone signalling and defense reactions. ROS production via plasma membrane-localized RBOHs is one of the earliest responses during pathogen infection in plants. Fusarium wilt is recognized as one of the most destructive banana diseases in the world that is caused by Fusarium oxysporium f. sp. cubense (Foc), a soil-borne fungus. Despite numerous reports on the involvement of ROS in Foc-banana interaction, rboh genes have not yet been identified in banana thus hindering the profiling of Marbohs expression in response to fusarium wilt infection. The aim of this study is to characterize rbohs in banana (Marbohs) and identify defense-related Marbohs through genome-wide and gene expression analysis in relation with hydrogen peroxide and electrolyte leakage level. In this study, we have identified nineteen Marbohs distributed on nine chromosomes of DH Pahang through database search. The functional domain organization of Marbohs include respiratory burst NADPH oxidase, EF-hand calcium binding domain (EFh), EF-hand domain pair (EFh-7), Nox/Duox transmembrane protein and NAD binding domain (NAD binding 6) are important for ROS production. Phylogenetic analysis clustered Marbohs into four subgroups and had a closer relationship with those from Manihot esculenta, Arabidopsis thaliana and Brassica rapa. Among all Marbohs, only MarbohB1 is located in subgroup III where most of the rbohs are related with plant defense response against pathogen. Based on the digital gene expression analysis of Marboh transcripts, MarbohB1 was significantly downregulated at 48 hpi and 96 hpi following Fusarium oxysporium f. sp. cubense Tropical Race 4 (FocTR4) infection. Based on the phylogenetic and digital gene expression analysis, MarbohB1 was chosen for further analysis in this study. The full length of Berangan MarbohB1 (MabrbohB1) was isolated via primer walking. The amino acid alignment of DH Pahang MarbohB1 and Berangan MabrbohB1 revealed 13 single nucleotide polymorphisms (SNPs) which caused 6 nonsynonymous and 6 synonymous amino acid changes in which 4 nonsynonymous occurred in conserve domains. The organ-specific and temporal expression analysis of MabrbohB1 upon hemibiotrophic fungal pathogen FocTR4 infection showed that MabrbohB1 was specifically expressed in root and exhibited a transient up-regulation after 2 hpi of FocTR4 inoculation, followed by down regulation at 48 hpi and 96 hpi. The increased expression was accompanied by steady increment of H2O2 level and electrolyte leakage in the infected root, suggesting that MabrbohB1 may be involved in defense responses in banana. Characterization of Marbohs and identification of MarbohB1 as defense-related gene add new knowledge about FocTR4-banana interaction and might be useful to counter fusarium wilt infection in the future. Overall, this research supports the suggested role of rboh genes in oxidative burst during plant response to pathogen.